Organizational commitment and job satisfaction affect nurse turnover intention - Hakim, Rosyida Nuur; Pratiwi, Arantika Meidya; Putri, Imram Radne Rimba; Anwar, Choirul (Alma Ata University Press, 2025)
Background: In Indonesia, the turnover prevalence rate was significantly high, recorded at 20.8% in 2019. The high turnover intention will have an impact on the high incidence of nurse transfer in the hospital so that it will become an obstacle for the hospital in providing health services to patients.Turnover typically begins with turnover intention, which can be influenced by organizational commitment and job satisfaction. The nurse turnover rate at Wonosari Regional Hospital remains within the normal range and has decreased over the past three years. However, preliminary study interviews with five inpatient nurses revealed that 3 out of the five nurses might consider seeking alternative employment and leaving the hospital if a better opportunity presented itself. Objectives: This study aims to determine the influence of organizational commitment and job satisfaction on nurse turnover intention at Wonosari Regional Hospital in 2024. Methods: This study is a quantitative study carried out by utilizing a cross-sectional design. The population consisted of inpatient nurses at Wonosari Regional Hospital, with a sample size of 131 nurses selected through proportional random sampling. Data were collected employing questionnaires and analyzed using logistic regression techniques.Results: The result of the study revealed a significant effect of organizational commitment on the turnover intentions of nurses at Wonosari Regional Hospital, with a significance level of 0.001 < 0.05. Similarly, job satisfaction also significantly influenced turnover intentions, with a significance level of 0.016 < 0.05. Conclusions: There is an influence between organizational commitment to nurse turnover intention. There is an influence between nurse job satisfaction to nurse turnover intention.